SAT0459 Significant association between periodontitis and risk of rheumatoid arthritis: A nationwide, population-based, case–control study. (23rd January 2014) - Chen, H.-H.; Huang, N.; Chen, Y.-M.; Chen, T.-J.; Chou, P.; Lee, Y.-L.; Chou, Y.-J.; Lan, J.-L.; Lai, K.-L.; Lin, C.-H.; Chen, D.-Y.
Abstract : Background: Although rheumatoid arthritis (RA) is associated with periodontitis, it remains unclear whether periodontitis is a significant risk factor for RA. Objectives: To investigate RA risk based on a history of periodontitis. Methods: The study is a nationwide, population-based, case–control study using administrative data. We identified 13, 779 newly-diagnosed RA cases (≥16 years) as the study cohort and 137, 790 non-RA patients matched for age, sex, and initial diagnosis date (index date) as controls. Using multivariate logistic regression analysis after adjustment for potential confounders, including age; urbanization level; geographic region; length of medical history before the index date; and a history of diabetes, osteoporosis, and Sjögren's syndrome, odds ratios (OR) with a 95% confidence interval (CI) were calculated to quantify the association between RA and periodontitis. External adjustment for smoking, a major unmeasured confounder, was performed. To evaluate the effect of periodontitis severity, and lag time since last periodontitis visit on the development of RA, ORs were calculated for subgroups of periodontitis patients according to the number of visits, cumulative cost, periodontal surgery, and time interval between last periodontitis visit and the index date. Results: An association between history of periodontitis and RA development (OR, 1.182; 95% CI, 1.140–1.225) was observed. The strength of this association remained statistically significant after adjustment for potential confounders (OR, 1.086; 95% CI, 1.047–1.127) and further adjustment for smoking using external information, or after variation of periodontal disease definitions. The association was dose- and time-dependent and was strongest when the interval between last periodontitis visit and the index date was. Conclusions: Periodontitis is not only a significant risk factor for RA with a dose–response relationship, but also a modest proximal risk factor for RA. References: Berthelot JM, Le Goff B. Rheumatoid arthritis and periodontal disease. Joint Bone Spine. Dec 2010;77(6):537-541. Arkema EV, Karlson EW, Costenbader KH. A prospective study of periodontal disease and risk of rheumatoid arthritis. J Rheumatol. Sep 2010;37(9):1800-1804. Smolik I, Robinson D, El-Gabalawy HS. Periodontitis and rheumatoid arthritis: epidemiologic, clinical, and immunologic associations. Compend Contin Educ Dent. May 2009;30(4):188-190, 192, 194 passim; quiz 198, 210. Ogrendik M. Rheumatoid arthritis is linked to oral bacteria: etiological association. Mod Rheumatol. 2009;19(5):453-456. de Pablo P, Dietrich T, McAlindon TE. Association of periodontal disease and tooth loss with rheumatoid arthritis in the US population. J Rheumatol. Jan 2008;35(1):70-76. Rosenstein ED, Greenwald RA, Kushner LJ, Weissmann G. Hypothesis: the humoral immune response to oral bacteria provides a stimulus for the development of rheumatoid arthritis. Inflammation. Dec 2004;28(6):311-318. Disclosure of Interest: None Declared